The possibilities of digital resources and LMS (Learning Management System) platforms in organizing independent learning for students - Utebaeva, N. (Zamonaviy ta’lim va tilshunoslik rivoji, 2026)
This article examines the role and opportunities of digital resources and LMS (Moodle, Canvas, Hemis) platforms in organizing students’ independent education under the credit-module system in higher education institutions. Pedagogical problems arising in the planning, management, and control of independent learning are analyzed, and effective methodical solutions are proposed to activate students’ educational and cognitive activities in the digital environment.